LEGISLATION INTRODUCED TO PROHIBIT SMOKING IN FEDERAL BUILDINGS (Tufts Archival Research Center, 2007)
Copy; Summary of the proposed "Ban on Smoking in Federal Buildings Act," H.R. 2118. Identifies the main provisions of the bill, chiefly the ban of smoking in federally-owned and maintained buildings, excluding VA hospitals, military installations, and federally owned housing. Cites Representative Traficant's rationale in proposing the bill as influenced by bans in the private sector and government expenses resulting from environmental tobacco smoke (ETS) exposure. Summarizes congressional findings on health effects of ETS.